2019
DOI: 10.1248/bpb.b18-00742
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Leaves of <i>Hydrangea serrata</i> and Their Anti-photoaging Effects on UVB-Irradiated Human Fibroblasts

Abstract: Hydrangea serrata (THUNB.) SER. (Hydrangeaceae) leaves have been used as herbal teas in Korea and Japan. The objective of this study was to identify anti-photoaging compounds in aqueous EtOH extract prepared from leaves of H. serrata and their effects on UVB-irradiated Hs68 human foreskin fibroblasts. Phytochemical study on H. serrata leaves led to the isolation and characterization of ten compounds: hydrangenol, thunberginol A, thunberginol C, hydrangenoside A, hydrangenoside C, cudrabibenzyl A, 2,3,4′-trihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
3
29
0
2
Order By: Relevance
“…Our recent phytochemical study showed that a variety of compounds isolated from H. serrata possess anti-photoaging activity in UVB-exposed human fibroblasts. Among these compounds, hydrangenol has potential protective effects on cell viability, production of procollagen type I, MMP-1, and pro-inflammatory cytokines [17]. Based on our previous report, we concluded that H. serrata may have the potential for application as a beneficial natural anti-photoaging agent.…”
Section: Introductionmentioning
confidence: 93%
“…Our recent phytochemical study showed that a variety of compounds isolated from H. serrata possess anti-photoaging activity in UVB-exposed human fibroblasts. Among these compounds, hydrangenol has potential protective effects on cell viability, production of procollagen type I, MMP-1, and pro-inflammatory cytokines [17]. Based on our previous report, we concluded that H. serrata may have the potential for application as a beneficial natural anti-photoaging agent.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, it appeared that the efficacy of pre-clinical and clinical trials could differ. Although the underlying mechanisms by which WHS improves skin wrinkles, hydration, elasticity, texture, and roughness were not investigated in this clinical trial, we suggest that the WHS supplement may have a positive effect on collagen decomposition based on the previous in vitro and in vivo studies [ 7 ]. Additionally, these preventive skin aging effects of WHS may be mediated through the anti-oxidative activities of hydrangenol, an active-constituent of H. serrata .…”
Section: Discussionmentioning
confidence: 97%
“…Hydrangea leaves have been consumed as traditional herbal tea and medicine in its native far-east Asian countries, including Korea, China, and Japan, and are known to have a distinctive mint-flavored sweet taste [ 29 ]. Hydrangea is native to the Korean mountains known as “San-su-guk, Mountain Hydrangea, or Tea of Heaven.” Our phytochemical study showed that a variety of compounds (hydrangenol, thunberginol A, thunberginol C, hydrangenoside A, hydrangenoside C, cudrabibenzyl A, 2,3,4′-trihydroxystilbene, thunberginol F, quercetin 3- O - β -D-xylopyranosyl (1–2)- β -D-galactopyranoside, quercetin 3- O - β -Dxylopyranosyl (1–2)- β -D-glucopyranoside, cudrabibenzyl A, 2,3,4′-trihydroxystilbene, quercetin 3- O - β -Dxylopyranosyl (1–2)- β -D-galactopyranoside, and quercetin 3- O - β -D-xylopyranosyl (1–2)- β -D-glucopyranoside) isolated from H. serrata possess anti-photoaging activity in UVB-exposed human fibroblasts [ 7 ]. Of these various compounds, hydrangenol was found to possesses potential protective effects on anti-photoaging properties in vitro and in vivo and then used as an active indicator compound [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations